Corporate Social Responsibility: Slack Resources and Board Gender Diversity - Purwanto, Eko; Rahmawati, Neng Euis (Jurnal Akuntansi, 2025)
Purpose – This study aims to analyze the influence of slack resources and board gender on the quality of CSR disclosure. Design/methodology/approach – This research employs a quantitative approach with a descriptive design. The data used consists of annual reports and sustainability reports obtained from the official website of the Indonesia Stock Exchange and the official websites of respective banking companies from 2019-2023. The sampling technique employed is purposive sampling, resulting in 65 samples from 13 banking companies. Data analysis techniques in this study include descriptive statistical analysis, classical assumption testing, multiple linear regression analysis, as well as correlation coefficient and determination coefficient tests. The hypotheses are tested using individual parameter significance tests (ttest) and simultaneous significance tests (F-test). Findings – Based on the analysis results, slack resources have an influence on CSR, the gender of the board commissioners does not affect CSR, the gender of the board directors has an influence on CSR, and both factors simultaneously have a significant impact on CSR in banking companies listed on the IDX during the period of 2019-2023. Research limitations/implications –The research population is limited to the banking sector only. Keywords: Board Gender, Corporate Social Responsibility, Slack Resources